A PIC-based wiper blade maintenance system: article - Suhairy, Mohd Shazni
This thesis presents the maintenance system of a wiper blade using Peripheral Interface Controller (PIC). The system consist of three main parts; Sensor, Microcontroller (PIC16F84A) and Motor. When the temperature is detected from the windscreen it will converted to a digital signal and sends it to the microcontroller (PIC16F84A) for processing purposed. MPLAB is the software use to download or programmed data into the controller by using PICkit to PIC16f84A. It will receive the converted outputs from the sensor and recognized the digital signals from the input pins. This PIC16F84A has been programmed according to certain instruction. Furthermore the PIC16F84A will send the digital output to the motor based on the desired inputs detected. The motor will be installed to the wiper and lift it up to avoid the blade from touching the windscreen that can make it defect.